(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Despite multiple nutritional programmes and iron supplementation therapies adopted over the past 50 years, Anaemia remains a highly prevalent condition in India. The underlying pathogenesis associated with Anaemia includes not only nutritional deficiencies, but also the issues with optimum absorption, bioavailability of food nutrients, and assimilation of absorbed nutrients. The current review comprises preliminary evidence on Raktda (MA 321), an Ayurvedic supplement for adjuvant or monotherapy use in long term treatment of Anaemia. Raktda has a holistic combination of ingredients including Mandoor Bhasma, Kant Lauh Bhasma, Praval Pishti, Muktashukti Pishti, Giloy Sattva, Yashtimadhu, Shilajit, Amalaki and many other herbs traditionally useful for treating all types of Anaemia and its associated morbidities. The synergy of herbs in Raktda reinstates normal physiology by functioning at five different levels: Agni, Pitta Dosha, Rasa Dhatu, Rakta Dhatu, and Rasayana. A small sample study (n = 16) on Raktda has shown an increase in mean Hb% from 9.231 to 11.046 (paired t-value= 8.5475, SE = 0.212, p<0.0001) - a change of mean by 1.815 points (95% CI = 1.353- 2.278), within a period of 30 days. Another study on Raktda (n = 47) has shown the beneficial effects of Raktda on increasing Hb% (7.16 to 11.13) and other anaemia symptoms such as fatigue, pain in legs, narcolepsy, anorexia, and faintness of skin. The current review outlines the need for conducting large scale investigations on Raktda, which can be used for treating Anaemia in the long run.